2017
DOI: 10.3389/fnint.2017.00015
|View full text |Cite
|
Sign up to set email alerts
|

Damaged Neocortical Perineuronal Nets Due to Experimental Focal Cerebral Ischemia in Mice, Rats and Sheep

Abstract: As part of the extracellular matrix (ECM), perineuronal nets (PNs) are polyanionic, chondroitin sulfate proteoglycan (CSPG)-rich coatings of certain neurons, known to be affected in various neural diseases. Although these structures are considered as important parts of the neurovascular unit (NVU), their role during evolution of acute ischemic stroke and subsequent tissue damage is poorly understood and only a few preclinical studies analyzed PNs after acute ischemic stroke. By employing three models of experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 97 publications
(130 reference statements)
5
34
0
1
Order By: Relevance
“…In contrast, in cortical areas surrounding the infarct and outside of the glial scar, WFA-expressing PNNs are completely degraded by day 7, and CSPG immunoreactivity is down regulated although they remain detectable up to 14 days post-injury ( Hobohm et al, 2005 ). Similar degradation of WFA-expressing PNNs in the neocortex has also been observed following thromboembolic middle cerebral artery occlusion in rats, permanent middle artery occlusion in mice, and focal cerebral ischemia in sheep ( Härtig et al, 2017 ). Interestingly, reduced PV-immunoreactivity and PV cell function have also been observed following stroke and this decrease in inhibitory cell function may underlie epilepsy-like activity following stroke ( Hobohm et al, 2005 ; Xie et al, 2014 ).…”
Section: Cns Injury and Strokesupporting
confidence: 64%
“…In contrast, in cortical areas surrounding the infarct and outside of the glial scar, WFA-expressing PNNs are completely degraded by day 7, and CSPG immunoreactivity is down regulated although they remain detectable up to 14 days post-injury ( Hobohm et al, 2005 ). Similar degradation of WFA-expressing PNNs in the neocortex has also been observed following thromboembolic middle cerebral artery occlusion in rats, permanent middle artery occlusion in mice, and focal cerebral ischemia in sheep ( Härtig et al, 2017 ). Interestingly, reduced PV-immunoreactivity and PV cell function have also been observed following stroke and this decrease in inhibitory cell function may underlie epilepsy-like activity following stroke ( Hobohm et al, 2005 ; Xie et al, 2014 ).…”
Section: Cns Injury and Strokesupporting
confidence: 64%
“…These data support the notion that removal of CS chains from CSPGs molecules allows alterations in the neural circuitry and results in increased plasticity (Fox and Caterson, 2002). Moreover, it appears that the numbers of PNNs, while generally stable in adult brain, can be dramatically decreased upon ischemia, seizures and traumatic brain injury (Hobohm et al, 2005;Harris et al, 2010;Karetko-Sysa et al, 2011;McRae et al, 2012;Yi et al, 2012;Härtig et al, 2017). In view of the above mentioned data, this decrease can be considered as an attempt of the impaired brain to reinstate plasticity in order to allow axonal sprouting and compensation of damaged function (Carmichael et al, 2017).…”
Section: The Brain Ecm Composition and Functionsupporting
confidence: 73%
“…It was reported that the glycan structures of CSPGs were affected in schizophrenia and epilepsy (Pantazopoulos et al, 2010 , 2015 ; Yutsudo and Kitagawa, 2015 ; Miyata and Kitagawa, 2016b ). PNNs are markedly reduced in experimental ischemic stroke models (Härtig et al, 2016 , 2017 ). Thus, it will be fascinating to assess the contribution of the molecular heterogeneity of PNN in models of these diseases.…”
Section: Discussionmentioning
confidence: 99%